Implementing Information Systems Plan in Malaysian Government Organisation: A Multiple Perspective Framework - Mohd. Yusof, Mokhtar; Wan Haniff, Ruzaina; Chua, Chong Oie (Malaysian Journal of Computer Science, 1998)
Summarises the limitations of the rationalistic approach for the design, implementation and appraisal of Information Systems Planning (ISP) and advances an interpretative cultural approach addressing the symbolic, boundary redefining and cultural attributes of ISP. Recognising both perspectives provides richer insights about the meaning and role of ISP in organisations. This suggests that managers, developers and researchers? efforts must embrace not only the instrumental technology of ISP, but the wider organisational and symbolic issues involved in the implementation of such systems.